Perception of Teachers to Sexuality Education in Secondary Schools: Exploring Teachers' Perception and Challenges in Implementing Sexuality Education in Secondary Schools (Journal of Advances and Scholarly Researches in Allied Education, 2023)
Schools have been seen as an important venue for advancing sexual health education. Thevast majority of responders (80) believed that sexuality education was necessary, and almost all (97).While 72 of respondents said that condoms should be made accessible to students in secondaryschools, 64 thought that condoms should not be included in sexuality education. All respondentsagreed that sexuality education raises knowledge of HIV and AIDS, and 92 agreed that it delays sexualdebut. Respondents were almost unanimous (96) in their belief that introducing sexuality educationinto schools increases condom usage. Forty-four percent said they felt the present sexuality educationlessons in schools were adequate. Sixty-eight percent of respondents said that knowledge aboutabortion and the ability to effectively communicate and negotiate are not formally taught in schools asmeans of reducing the spread of HIV and other STDs and the likelihood of unintended pregnancies. Sixtypercent of respondents cited cultural norms and a lack of training as the primary obstacles to sexualeducation. Sixty-four percent of educators said they had never received sexuality education training.Secondary school teachers in Gaborone have a generally good attitude towards and understanding ofsexuality education. The primary challenges to implementing sexuality education in secondary schoolsare cultural and pedagogical. Teachers' sexuality education knowledge and attitudes may both benefitfrom in-service education. There has to be a revision of the curriculum to incorporate comprehensivesexuality education.